Little dragons prefer flowers to maidens: a lizard that laps nectar and pollinates trees - Sazima, Ivan (2005)
Lizards rarely visit and pollinate flowers, the few recent records being mostly restricted to island habitats. We report here on the Noronha skink (Euprepis atlanticus) seeking nectar in the flowers of the leguminous mulungu tree (Erythrina velutina) at Fernando de Noronha Archipelago, off northeast Brazil. The mulungu tree blooms during the dry season, and each flower secretes copious and diluted nectar throughout the day. The Noronha skink climbs up to the inflorescences and laps the nectar accumulated in the flowers' base. While exploiting the flowers and crawling over the inflorescences, the body parts of the skink contact the anthers and stigmas and pollen adheres to the lizard's scales. The lizard visits inflorescences from the same and different trees, which renders it a potential pollinator. As the mulungu tree blooms during the dry season and the island has little or no natural freshwater supply during drought periods, we suggest that the Noronha skink seeks flower nectar both for its energetic, diluted sugars and the water content.